The Book of Snobs - Thackeray, William Makepeace, 1811-1863 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Book of Snobs" by William Makepeace Thackeray is a collection of satirical works published in 1848. Originally appearing as weekly pieces in Punch magazine, this sharp social commentary dissects the snobbery permeating Victorian society in England and France. Thackeray skewers those who "give importance to unimportant things" and "meanly admire mean things," examining various social groups with biting wit. The immensely popular work thrust Thackeray into public prominence and helped popularize the very term "snob" itself, establishing what scholars call "the baptism of snobbery." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Book_of_Snobs
Release date is 2006-05-25
Produced by Sean Hackett; David Widger
Keywords: Snobs and snobbishness -- Humor